Controllability of linear stochastic systems in Hilbert spaces - Mahmudov, NI (Academic Press Inc, 2001)
The classical theory of controllability for deterministic systems is extended to linear stochastic systems defined on infinite-dimensional Hilbert spaces. Three types of stochastic controllability are studied: approximate, complete, and S-controllability. Tests for complete, approximate, and S-controllabilities are proved and the relation between the controllability of linear stochastic systems and the controllability of the corresponding deterministic Systems is studied. (C) 2001 Academic Press.
Keywords: controllability; stochastic controllability; linear system